ICEBERG study: an indirect adjusted comparison estimating the long-term benefit of esketamine nasal spray when compared with routine treatment of treatment resistant depression in general psychiatry - Oliveira-Maia, Albino J.; Morrens, Joachim; Rive, Benoit; Godinov, Yordan; Cabrieto, Jedelyn; Perualila, Nolen; Barbreau, Sebastien; Mulhern-Haughey, Siobhán (Frontiers in Psychiatry, 2023)
Background Treatment resistant depression (TRD) affects 10–30% of patients with major depressive disorder. In 4-week trials, esketamine nasal spray (NS) was efficacious vs. placebo when both were initiated in addition to a new selective serotonin or serotonin norepinephrine reuptake inhibitor. However, comparison with an extended range of real-world treatments (RWT) is lacking. Methods ICEBERG was an adjusted indirect treatment comparison using propensity score-based inverse probability weighting, performed on 6-month response and remission data from patients receiving esketamine NS plus oral antidepressant from the SUSTAIN-2 (NCT02497287; clinicaltrials.gov) study, compared with patients receiving other RWT from the European Observational TRD Cohort (EOTC; NCT03373253; clinicaltrials.gov) study. SUSTAIN-2 was a long-term open-label study of esketamine NS, while the EOTC was conducted at a time when esketamine NS was not available as RWT. Threshold and sensitivity analyses were conducted to assess how robust the primary analyses were. Results Patients receiving esketamine NS had a higher probability of 6-month response (49.7% [95% confidence interval (CI) 45.6–53.9]) and remission (33.6% [95% CI 29.7–37.6]) vs. patients receiving RWT (26.4% [95% CI 21.5–31.4] and 18.2% [95% CI 13.9–22.5], respectively), according to rescaled average treatment effect among treated estimates. Resulting adjusted odds ratios (OR) and relative risk (RR) favoured esketamine NS over RWT for 6-month response (OR 2.756 [95% CI 2.034–3.733], p < 0.0001; RR 1.882 [95% CI 1.534–2.310], p < 0.0001) and remission (OR 2.276 [95% CI 1.621–3.196], p < 0.0001; RR 1.847 [95% CI 1.418–2.406], p < 0.0001). Threshold analyses suggested that differences between the two studies were robust, and results were consistent across extensive sensitivity analyses. Conclusion ICEBERG supports that, at 6 months, esketamine NS has a substantial and significant benefit over RWT for patients with TRD. While results may be affected by unobserved confounding factors, threshold analyses suggested these were unlikely to impact the study conclusions. To view an animated summary of this publication, please click on the Supplementary video.